The Level of IT-business Strategic Alignment and Its Impact on Organizational Excellence: A Study of the Jordanian Mining Sector - Al-adaileh, Raid Mohd (International Review of Management and Marketing, 2017)
This study measures the level of IT-business strategic alignment and its impact on organizational excellence as perceived by managers of the Jordanian mining sector working in managerial positions. The study is a quantitative study that is based on the use of a questionnaire which is designed for the purpose of this study a comprehensive sampling strategy is used to select the participants due to the limited population size (managerial positions). 150 questionnaires were personally distributed. 117 were analyzed. SPSS.22 and AMOS.23 are used to analyses the data and to test the study hypotheses. The study revealed that the level of IT-business strategic alignment as well as the level of organizational excellence within the context of Jordanian Mining Sector are medium as perceived by managers. The study also found that the level of IT-business strategic alignment has a direct significant statistical impact on the overall organizational excellence and its five proposed dimensions as perceived by managers. Keywords: Strategic Alignment, Excellence, Information Technology, IT-business Alignment, Culture, Leadership JEL Classifications: L1, L86